Surgical rejuvenating for the aged earlobe: a technical innovation - Miguel Marques de Oliveira; Gustavo de Sousa Marques de Oliveira (Revista Brasileira de Cirurgia Plástica, 2022)
ABSTRACT The authors present a new surgical approach to the aging earlobe. The technique is based on the classic marginal reduction technique of the earlobe contour that has been improved. In essence, it seeks to preserve the subdermal fat layer of the distal flap created for the purpose of raising the earlobe while being shortened, thickened and smooth, in a hidden scar. It is a tripartite resolution to this problem never seen in the relevant literature. Four 68-year-old women were treated: the first with the classic manner in 2009 and the others with this modification to improve the earlobe withered appearance in 2017-2019. The study shows a rejuvenating eutrophic reduction technique.